Pentingnya Konsep Pembelajaran Daring dalam Meningkatkan Kompetensi Guru di Masa Pandemi Covid-19 - Muhassanah, Nur’aini; Winarni, Ambar (Literasi Jurnal Pengabdian Masyarakat dan Inovasi, 2022)
The purpose of this Community Service activity is to increase teacher competence in online learning during the Covid-19 pandemic. Some of the difficulties experienced by teachers during online learning are related to learning media, preparation of lesson plans and assessments. This PKM activity is in a virtual form, namely a Webinar which is carried out through the Zoom Meeting media. Where this activity is in collaboration with KKKS Mustika Dwija Sarana Sumpiuh with 240 participants as teachers. The method used is Service Learning. The results of this activity are able to increase teacher competence in the online learning process related to three things, namely first, the use of online learning media other than WA Group such as Zoom/GMeet, Google Classroom, and Learning Videos; second, increasing teacher competence in preparing online learning lesson plans or blended learning, and third, increasing teacher competence in preparing online learning assessments